Two new species and a new synonym of Neoperla (Plecoptera: Perlidae) from China, with proposal of a new species group - Li, Weihai; Yan, Yanhua (Zootaxa, 2021)
Two new species of the stonefly genus Neoperla, N. jiangae sp. nov. and N. jiaoxihe sp. nov., are described from Shaanxi Province of northwest China. The new species are compared with related congeners. Neoperla flagellata Li & Murányi, 2012 (in Li et al. 2012b) is placed as a synonym of N. bicornua Wu, 1973. The Neoperla sinensis species subgroup in the N. montivaga group is proposed and defined.